Considerações sobre a modelagem matemática em uma perspectiva de educação matemática - BURAK, Dionísio (Universidade Federal do Pará, 2020)
This article presents a theoretical discussion about Mathematical Modeling into a perspective in Mathematics Education designed as a Human and Social Science. In this context, the aim is to estabilish relationships and justify the referrals on Modeling as understood by Burak (2004) in harmony with the comprehension of Mathematics Education. What is sought, in methodological terms, is to conduct orderly ideas, crossing elements of the present theoretical framework and the vision of the discussed Modeling, as well as exemplifying the development of stages on Mathematics Modeling.